Wear-resistant functional denture base material and production process thereof

By using wear-resistant additives and functional composites of nano-hydroxyapatite and sepiolite fibers in denture base materials, the problems of poor scratch resistance and lack of antibacterial properties are solved, and the wear resistance of the material is significantly improved and antibacterial properties, extend service life and protect oral health.

CN119488437AActive Publication Date: 2025-02-21ZHUHAI REFINE MEDICAL EQUIP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411636082.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

During use, existing denture base materials have problems such as poor scratch resistance and lack of antibacterial properties, which lead to material wear and microorganism growth, shorten service life and affect oral health.

Method used

Using nano-hydroxyapatite and sepiolite fibers as wear-resistant additives, they are organically combined with polymethyl methacrylate matrix materials through the organic modification technology of liquid-terminal carboxyfluororubber to prepare functional composites , improve the material's wear resistance and antibacterial properties.

Benefits of technology

It significantly improves the hardness, wear resistance and antibacterial properties of denture base materials, extends the service life, reduces the probability of wear and abrasion, reduces the frequency of denture base replacement, and effectively prevents microbial erosion and protects oral health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488437A_ABST
    Figure CN119488437A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of denture base materials, and discloses a wear-resistant functional denture base material and a production process thereof.The denture base material is prepared from polymethyl methacrylate, denture water, an initiator, an accelerant, a wear-resistant additive and a functional compound. According to the denture base material disclosed by the invention, a dispersion enhancing effect can be achieved in the denture base material, the wear rate of the denture base material is reduced, the hardness and wear resistance of the denture base material are improved, and the replacement frequency of the denture base is reduced; by adding the functional compound, a toughening effect can be achieved, the bending strength of the denture base material is improved, the denture base material is prevented from being broken, the denture base material is endowed with long-term antibacterial performance, corrosion of microorganisms to the denture base material is reduced, and the service life of the denture base is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of denture base materials, and in particular to a wear-resistant functional denture base material and a production process thereof. Background Art

[0002] With the continuous improvement of living standards and the aggravation of population aging, people pay more attention to oral health, and the demand for dentures is also increasing. Dentures, also known as false teeth, help chewing food, maintain facial contours, prevent tooth displacement, prevent oral diseases, improve pronunciation, etc., which are of great significance to improving the quality of life. Denture base is an important component of full dentures, providing support and attachment basis for artificial teeth, reducing pressure and discomfort on oral tissues, and preventing dentures from moving or falling off in the mouth. Denture base materials are usually made of resin materials or metal materials. Denture bases made of metal materials may cause allergies and are heavy and expensive. Therefore, research on resin materials as denture base materials is very necessary.

[0003] Polymethyl methacrylate (PMMA) is a medical polymer material, also known as organic glass. It has the advantages of stable chemical properties, excellent transparency and gloss, non-toxic and environmentally friendly, light weight, easy processing, good biocompatibility, and not easy to cause allergies. It is a good material for preparing denture bases. However, polymethyl methacrylate also has shortcomings. The surface hardness of polymethyl methacrylate is not high and it is not scratch-resistant. During use, the surface is prone to wear and scratching, causing the denture base to break and be damaged. In addition, polymethyl methacrylate does not have antibacterial properties. Microorganisms can easily grow on the surface of the denture base to form plaque, which leads to erosion of the denture base material, shortening the service life of the denture base, and causing oral diseases, which is not conducive to oral health. Therefore, it is very necessary to improve the wear resistance and antibacterial properties of polymethyl methacrylate materials. The patent with publication number CN108743403B discloses a composite material for denture bases that can continuously release negative ions. Nano-silica particles are generated in situ on the surface of hokutolite, and then acrylic acid monomers are grafted onto the surface of the nano-silica to obtain a composite material with the chemical structure homologous to polymethyl methacrylate, a denture base material. The dispersion of hokutolite is promoted, the compatibility of the two is optimized, and the mechanical properties of the denture base material are improved. At the same time, the addition of nano-silica makes the material present better physical and mechanical properties. However, the patent does not take into account the important role of wear resistance and antibacterial properties of denture base materials in practical applications. Therefore, the present invention provides a denture base material with excellent wear resistance and antibacterial properties, and can also increase the service life of the denture base material. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a wear-resistant functional denture base material and a production process thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A wear-resistant functional denture base material comprises the following raw materials in parts by weight: 85-100 parts of polymethyl methacrylate, 80-90 parts of denture water, 1-3 parts of initiator, 0.2-0.5 parts of accelerator, 3-6 parts of wear-resistant additives and 2.5-5.5 parts of functional composites.

[0007] Furthermore, the dental tray water is methyl methacrylate; the initiator is di-tert-butyl peroxide or benzoyl peroxide; and the accelerator is sodium p-toluenesulfinate.

[0008] Furthermore, the preparation method of the wear-resistant additive comprises the following steps:

[0009] Step S1: adding nano-hydroxyapatite to deionized water, and dispersing by ultrasonic method to form a nano-hydroxyapatite suspension; adding sepiolite fiber to deionized water, and dispersing by ultrasonic method to form a sepiolite fiber suspension; and mixing the two suspensions to obtain a mixed suspension;

[0010] Step S2: Take liquid carboxyl-terminated fluororubber and add it to N,N-dimethylformamide, add the mixed suspension, stir evenly, increase the temperature to 80-90°C, add the catalyst, stir the reaction for 4-6 hours, separate the product, wash, and dry to obtain a wear-resistant additive.

[0011] By adopting the above technical scheme, the hydroxyl groups on the surface of nano-hydroxyapatite and the hydroxyl groups on the surface of sepiolite fiber can undergo esterification reaction with the carboxyl groups in the structure of liquid carboxyl-terminated fluororubber under the action of a catalyst, thereby organically combining the nano-hydroxyapatite and sepiolite fiber to obtain a wear-resistant additive. The wear-resistant additive prepared by the present invention takes nano hydroxyapatite and sepiolite fibers as a matrix and is organically modified by using liquid end carboxyl fluororubber, thereby effectively improving the compatibility of nano hydroxyapatite and sepiolite fibers with the matrix and avoiding the agglomeration of nano hydroxyapatite and sepiolite fibers in the matrix material. The wear-resistant additive is dispersed in the matrix material and can be evenly dispersed to play a role of dispersion enhancement. It can effectively bear the load as a rigid support point, improve the hardness, reduce the cutting effect of abrasive particles, reduce the wear rate of the matrix material, and improve the wear resistance. At the same time, the combination of the two can produce a ball effect, change the friction form from sliding friction to a mixed form of sliding and rolling friction, effectively slow down the crack expansion, and reduce wear. In addition, the fluorine-containing molecular chain can reduce the surface energy of the nano hydroxyapatite and sepiolite fibers, help to maintain a low friction coefficient of the matrix material, and can also inhibit the serious abrasive wear caused by agglomeration, play a synergistic wear-resistant role, thereby effectively improving the wear resistance of the denture base material, reducing the probability of wear and abrasion, and reducing the replacement frequency of the denture base.

[0012] Furthermore, in step S1, the mass fraction of the nano-hydroxyapatite suspension is 1-3%; the mass fraction of the sepiolite fiber suspension is 2-5%.

[0013] Furthermore, in step S2, the catalyst is p-toluenesulfonic acid or calcium methanesulfonate.

[0014] Furthermore, the method for preparing the functional complex comprises the following steps:

[0015] Step A: adding sodium borohydride to dimethyl sulfoxide, introducing nitrogen, raising the temperature to 115-125° C., adding polyetheretherketone, and after 6-8 hours, separating the product, washing, and drying to obtain hydroxylated polyetheretherketone;

[0016] Step B: Add hydroxylated polyetheretherketone to N,N-dimethylformamide, add p-coumaric acid and p-toluenesulfonic acid, heat to react, separate the product, and cool to room temperature to obtain a functional complex.

[0017] By adopting the above technical scheme, under the reducing action of sodium borohydride, the carbonyl group in the polyetheretherketone can be reduced to a hydroxyl group to obtain a hydroxylated polyetheretherketone. Under the action of p-toluenesulfonic acid, the hydroxyl group of the hydroxylated polyetheretherketone can undergo an esterification reaction with the carboxyl group in the p-coumaric acid structure to obtain a functional complex. The polyetheretherketone in the functional composite structure prepared by the present invention has good mechanical properties and biosafety, and can be applied to denture base materials. The functional composite structure contains introduced hydroxyl groups, which can produce hydrogen bonds with ester groups in the polymethyl methacrylate matrix structure to form a semi-interpenetrating polymer network structure, which enhances the density and stability of the matrix material to a certain extent, can play a role in toughening the matrix material, improve the bending strength of the matrix material, and avoid the denture base from being easily broken. At the same time, the natural antibacterial substance p-coumaric acid is introduced into the structure, which has a broad-spectrum antibacterial effect, can exist in the matrix material for a long time, will not easily migrate or precipitate, and has a long-lasting antibacterial effect, which is beneficial to reducing oral diseases caused by microorganisms, reducing the probability of plaque generation, reducing the degree of damage to the denture base material, and extending the service life of the denture base.

[0018] Furthermore, in step B, the temperature of the heating reaction is set to 85-100° C. and the time is 6-8 hours.

[0019] A production process of a wear-resistant functional denture base material comprises the following steps:

[0020] Step 1: Stir and mix polymethyl methacrylate, initiator, wear-resistant additive and functional compound to obtain a mixed base material;

[0021] Step 2: Add denture water and accelerator to the mixed base material, stir for 10-30 minutes, and after it forms a mass, transfer it to a mold. Heat the mold in a constant temperature water bath at 70-80°C for 1-2 hours, then increase the temperature to 90-110°C and heat at a constant temperature for 40-60 minutes to obtain the denture base material.

[0022] Beneficial effects of the present invention:

[0023] The present invention adds wear-resistant additives and functional composites into the preparation process of denture base materials, so that the prepared denture base materials have the characteristics of high hardness, excellent wear resistance, good bending strength and excellent antibacterial performance, which can reduce the probability of wear and abrasion, reduce the replacement frequency of denture base materials, avoid fracture of denture base materials, prevent microorganisms from eroding denture base materials, resulting in shortened service life and harm to oral health.

[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0026] Figure 1 The scanning electron microscope images of the sepiolite fiber and the wear-resistant additive in the present invention, wherein (A) is the sepiolite fiber and (B) is the wear-resistant additive;

[0027] Figure 2 It is the infrared spectrum of the functional complex in the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The preparation methods of the wear-resistant additives and functional composites in the following examples and comparative examples are as follows:

[0030] 1. Preparation of wear-resistant additives

[0031] Step S1: adding nano-hydroxyapatite to deionized water, and dispersing by ultrasonic method to form a nano-hydroxyapatite suspension with a mass fraction of 2%, adding sepiolite fiber to deionized water, and dispersing by ultrasonic method to form a sepiolite fiber suspension with a mass fraction of 4%, and mixing the two suspensions to obtain a mixed suspension;

[0032] Step S2: Take 3 g of liquid carboxyl-terminated fluororubber and add it to N,N-dimethylformamide, add 250 mL of the mixed suspension, stir evenly, raise the temperature to 90°C, add 1.5 g of p-toluenesulfonic acid, stir the reaction for 6 hours, separate the product, wash, and dry to obtain a wear-resistant additive.

[0033] The morphology of sepiolite fibers and wear-resistant additives was observed using a Hitachi-S-2150 scanning electron microscope. Figure 1 As can be seen from the figure, (A) is the smooth surface of the sepiolite fiber without attachments, and (B) is the surface of the wear-resistant additive grafted with particles. It can be seen that nano-hydroxyapatite and sepiolite fiber have achieved an organic combination.

[0034] 2. Preparation of functional complexes

[0035] Step A: 120 mg of sodium borohydride was added to dimethyl sulfoxide, nitrogen was introduced, the temperature was raised to 120° C., 5.5 g of polyetheretherketone was added, and after 8 hours, the product was separated, washed, and dried to obtain hydroxylated polyetheretherketone;

[0036] Step B: Add 5 g of hydroxylated polyetheretherketone to N,N-dimethylformamide, add 3.8 g of p-coumaric acid and 1.8 g of p-toluenesulfonic acid, heat to 95°C, react for 6 hours, separate the product, and cool to room temperature to obtain a functional complex.

[0037] The functional complex was tested by infrared spectrometer Nicolet iS10. Figure 2 As shown, analysis shows that in the infrared spectrum of the functional complex, 3346cm -1 The absorption peak of hydroxyl group appeared at 3045cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appeared at 3018 cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 1748 cm -1 The absorption peak of the carbon-oxygen double bond in the ester group appeared at 1713 cm -1 The absorption peak of the carbon-oxygen double bond in the carbonyl group appeared at .

[0038] Example 1

[0039] Production of denture base materials

[0040] Step 1: 85 g of polymethyl methacrylate, 1 g of benzoyl peroxide, 3 g of wear-resistant additive, and 2.5 g of functional compound are stirred and mixed to obtain a mixed base material;

[0041] Step 2: Add 80g of methyl methacrylate and 0.2g of sodium p-toluenesulfinate to the mixed base material, stir for 10 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 70°C for 1 hour, then increase the temperature to 90°C and heat at a constant temperature for 40 minutes to obtain the denture base material.

[0042] Example 2

[0043] Production of denture base materials

[0044] Step 1: 90 g of polymethyl methacrylate, 2 g of benzoyl peroxide, 4 g of wear-resistant additive, and 3.5 g of functional compound are stirred and mixed to obtain a mixed base material;

[0045] Step 2: Add 85g of methyl methacrylate and 0.3g of sodium p-toluenesulfinate to the mixed base material, stir for 20 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 75°C for 1.5 hours, then increase the temperature to 100°C and heat at a constant temperature for 50 minutes to obtain the denture base material.

[0046] Example 3

[0047] Production of denture base materials

[0048] Step 1: 95 g of polymethyl methacrylate, 2.5 g of benzoyl peroxide, 5 g of wear-resistant additive, and 4.5 g of functional compound are stirred and mixed to obtain a mixed base material;

[0049] Step 2: Add 85g of methyl methacrylate and 0.4g of sodium p-toluenesulfinate to the mixed base material, stir for 25 minutes, and after it is agglomerated, transfer it to a mold. Heat the mold in a constant temperature water bath at 75°C for 1.5 hours, then increase the temperature to 105°C and heat at a constant temperature for 55 minutes to obtain the denture base material.

[0050] Example 4

[0051] Production of denture base materials

[0052] Step 1: 100 g of polymethyl methacrylate, 3 g of benzoyl peroxide, 6 g of wear-resistant additive, and 5.5 g of functional compound are stirred and mixed to obtain a mixed base material;

[0053] Step 2: Add 90g of methyl methacrylate and 0.5g of sodium p-toluenesulfinate to the mixed base material, stir for 30 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 80°C for 2 hours, then increase the temperature to 110°C and heat at a constant temperature for 60 minutes to obtain the denture base material.

[0054] Comparative Example 1

[0055] Production of denture base materials

[0056] Step 1: 90g of polymethyl methacrylate, 2g of benzoyl peroxide, and 4g of wear-resistant additive are stirred and mixed to obtain a mixed base material;

[0057] Step 2: Add 85g of methyl methacrylate and 0.3g of sodium p-toluenesulfinate to the mixed base material, stir for 20 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 75°C for 1.5 hours, then increase the temperature to 100°C and heat at a constant temperature for 50 minutes to obtain the denture base material.

[0058] Comparative Example 2

[0059] Production of denture base materials

[0060] Step 1: 90 g of polymethyl methacrylate, 2 g of benzoyl peroxide, and 3.5 g of the functional compound are stirred and mixed to obtain a mixed base material;

[0061] Step 2: Add 85g of methyl methacrylate and 0.3g of sodium p-toluenesulfinate to the mixed base material, stir for 20 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 75°C for 1.5 hours, then increase the temperature to 100°C and heat at a constant temperature for 50 minutes to obtain the denture base material.

[0062] Comparative Example 3

[0063] Production of denture base materials

[0064] Step 1: 90 g of polymethyl methacrylate, 2 g of benzoyl peroxide, 2 g of nano-hydroxyapatite, 2 g of sepiolite fiber, and 3.5 g of the functional composite are stirred and mixed to obtain a mixed base material;

[0065] Step 2: Add 85g of methyl methacrylate and 0.3g of sodium p-toluenesulfinate to the mixed base material, stir for 20 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 75°C for 1.5 hours, then increase the temperature to 100°C and heat at a constant temperature for 50 minutes to obtain the denture base material.

[0066] Comparative Example 4

[0067] Production of denture base materials

[0068] Step 1: 90 g of polymethyl methacrylate, 2 g of benzoyl peroxide, 4 g of wear-resistant additive, and 3.5 g of p-coumaric acid are stirred and mixed to obtain a mixed base material;

[0069] Step 2: Add 85g of methyl methacrylate and 0.3g of sodium p-toluenesulfinate to the mixed base material, stir for 20 minutes, and after it is clumped, transfer it to a mold. Heat the mold in a constant temperature water bath at 75°C for 1.5 hours, then increase the temperature to 100°C and heat at a constant temperature for 50 minutes to obtain the denture base material.

[0070] Performance Testing

[0071] The denture base materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were prepared into samples that met the test standards. The hardness of the samples was tested according to the standard GB / T 2411-2008. The wear resistance of the samples was tested according to the standard GB / T 5478-2008. The bending strength of the samples was tested according to the standard GB / T 9341-2008. After the samples were placed for 60 days, the antibacterial properties of the samples were tested by the following method: 1 mL of a 10 -5 CFU / mL of Staphylococcus aureus liquid was added to the surface of the sterilized sample and cultured in a 35°C environment for 6 hours. 20 μL of the liquid was evenly spread on the culture medium. After culturing in a 35°C environment for 24 hours, the number of colonies in the culture medium was counted as W, and a blank test was performed. The number of colonies in the culture medium was counted as X. The antibacterial rate was calculated using the formula: Antibacterial rate (%) = [(XW) / X] × 100%. The test results are shown in the following table:

[0072] Hardness (HD) Wear rate (%) Bending strength(MPa) Antibacterial rate (%) Example 1 60.9 0.16 117.6 99.6 Example 2 62.3 0.11 118.6 99.9 Example 3 61.5 0.14 117.9 99.7 Example 4 61.8 0.13 118.4 99.8 Comparative Example 1 60.1 0.21 65.8 56.3 Comparative Example 2 42.3 1.29 116.8 99.0 Comparative Example 3 51.5 0.86 117.1 99.4 Comparative Example 4 60.1 0.19 68.8 62.6

[0073] It can be seen from the above table that the denture base materials prepared in Examples 1 to 4 of the present invention have the characteristics of high hardness, excellent wear resistance, good bending strength, excellent antibacterial properties, etc. Comparative Example 1 adds wear-resistant additives but does not add functional composites, and has excellent hardness and wear resistance, but poor bending strength and antibacterial properties; Comparative Example 2 adds functional composites but does not add wear-resistant additives, and has excellent bending strength and antibacterial properties, but poor hardness and wear resistance; Comparative Example 3 adds nano-hydroxyapatite, sepiolite fibers and functional composites, and the unmodified nano-hydroxyapatite and sepiolite fibers agglomerate in the matrix material, which has poor improvement effects on hardness and wear resistance, and cannot utilize fluorine-containing molecular chains to reduce surface energy, inhibit abrasive wear, and improve wear resistance, so the hardness and wear resistance are poor, and the bending strength and antibacterial properties are excellent; Comparative Example 4 adds wear-resistant additives and p-coumaric acid, and has excellent hardness and wear resistance, but because p-coumaric acid is a small molecule natural antibacterial substance, it is easy to migrate or precipitate in the matrix, so the antibacterial properties are poor, and polyetheretherketone cannot be used to improve the bending strength of the matrix material, so the bending strength is poor.

[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A wear-resistant functional denture base material, characterized in that: The invention comprises the following raw materials in parts by weight: 85-100 parts of polymethyl methacrylate, 80-90 parts of dental tray water, 1-3 parts of initiator, 0.2-0.5 parts of accelerator, 3-6 parts of wear-resistant additive and 2.5-5.5 parts of functional compound.

2. The wear-resistant functional denture base material according to claim 1, characterized in that: The denture water is methyl methacrylate; the initiator is di-tert-butyl peroxide or benzoyl peroxide; and the accelerator is sodium p-toluenesulfinate.

3. The wear-resistant functional denture base material according to claim 1, characterized in that: The preparation method of the wear-resistant additive comprises the following steps: Step S1: adding nano-hydroxyapatite to deionized water, and dispersing by ultrasonic method to form a nano-hydroxyapatite suspension; adding sepiolite fiber to deionized water, and dispersing by ultrasonic method to form a sepiolite fiber suspension; and mixing the two suspensions to obtain a mixed suspension; Step S2: Take liquid carboxyl-terminated fluororubber and add it to N,N-dimethylformamide, add the mixed suspension, stir evenly, increase the temperature to 80-90°C, add the catalyst, stir the reaction for 4-6 hours, separate the product, wash, and dry to obtain a wear-resistant additive.

4. The wear-resistant functional denture base material according to claim 3, characterized in that: In step S1, the mass fraction of the nano-hydroxyapatite suspension is 1-3%; the mass fraction of the sepiolite fiber suspension is 2-5%.

5. The wear-resistant functional denture base material according to claim 3, characterized in that: In step S2, the catalyst is p-toluenesulfonic acid or calcium methanesulfonate.

6. The wear-resistant functional denture base material according to claim 1, characterized in that: The method for preparing the functional composite comprises the following steps: Step A: adding sodium borohydride to dimethyl sulfoxide, introducing nitrogen, raising the temperature to 115-125° C., adding polyetheretherketone, and after 6-8 hours, separating the product, washing, and drying to obtain hydroxylated polyetheretherketone; Step B: Add hydroxylated polyetheretherketone to N,N-dimethylformamide, add p-coumaric acid and p-toluenesulfonic acid, heat to react, separate the product, and cool to room temperature to obtain a functional complex.

7. The wear-resistant functional denture base material according to claim 6, characterized in that: In step B, the temperature of the temperature-raising reaction is set to 85-100° C. and the time is 6-8 hours.

8. A production process for the wear-resistant functional denture base material according to claim 1, characterized in that: The following steps are involved: Step 1: Stir and mix polymethyl methacrylate, initiator, wear-resistant additive and functional compound to obtain a mixed base material; Step 2: Add denture water and accelerator to the mixed base material, stir for 10-30 minutes, and after it forms a mass, transfer it to a mold. Heat the mold in a constant temperature water bath at 70-80°C for 1-2 hours, then increase the temperature to 90-110°C and heat at a constant temperature for 40-60 minutes to obtain the denture base material.

Citation Information

Patent Citations

  • A composite material for denture bases that continuously releases negative ions

    CN108743403B

  • Anti-antibacterial complete denture and preparation method thereof

    CN110384616A

  • Medical beauty antibacterial denture base material and preparation method thereof

    CN111789771A

  • Movable denture and manufacturing method thereof

    CN116602875A

  • Dental antibacterial false tooth base material

    CN1977787A